2009
DOI: 10.1097/mpa.0b013e318187eb3f
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Determinants of Adjuvant Therapy Among Older Patients Who Receive Curative Surgery for Pancreatic Cancer

Abstract: OBJECTIVE We conducted a population-based study to describe the utilization, determinants, and survival effects of adjuvant therapies following surgery among older patients with pancreatic cancer. METHODS Using SEER-Medicare data, we identified patients >65 years who received surgical resection for pancreatic cancer during 1992–2002. We constructed multiple logistic regression models to examine patient, clinical, and hospital factors associated with receiving adjuvant therapy. Cox proportional hazards models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 16 publications
2
34
1
Order By: Relevance
“…In addition, we identified a trend of increasing gemcitabine utilization with increasing SES. These findings are consistent with previous reports in earlier stage pancreatic cancer in regard to adjuvant therapy after resection (14) and in patients with stage III pancreatic cancer in the SEER-Medicare population (15), where receipt of any treatment is more common in those who are married and of higher SES status. The magnitude of SES as an independent variable was large, with patients in the top quintile more than twice as likely to receive gemcitabine as those in the lowest quintile.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we identified a trend of increasing gemcitabine utilization with increasing SES. These findings are consistent with previous reports in earlier stage pancreatic cancer in regard to adjuvant therapy after resection (14) and in patients with stage III pancreatic cancer in the SEER-Medicare population (15), where receipt of any treatment is more common in those who are married and of higher SES status. The magnitude of SES as an independent variable was large, with patients in the top quintile more than twice as likely to receive gemcitabine as those in the lowest quintile.…”
Section: Discussionsupporting
confidence: 92%
“…Gemcitabine was approved as a first-line agent on the basis of a pivotal phase III trial (4), which demonstrated improvement in clinical control (measured by pain control, functional status, and weight) Many studies have demonstrated that there are significant disparities in utilization of appropriate therapy and outcomes in advanced cancers based on sociodemographic variables, including age (5), race/ethnicity (6)(7)(8), education (9) socioeconomic status (10)(11)(12), and gender (13). Previous studies in pancreatic cancer have noted variations in the utilization of adjuvant therapy after resection of localized pancreatic cancer (14) and in patients with stage III disease (15). We are now looking at these factors in the treatment of stage IV pancreatic cancer with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on large national databases have demonstrated that black patients in the general population are less likely to undergo surgical resection and less likely to receive adjuvant therapy for locoregional PDAC than white patients. [2][3][4][5][6]9,15 Murphy et al demonstrated that black patients with locoregional pancreatic cancer are less likely to see a medical oncologist, radiation oncologist, and surgeon, and are less likely to receive surgery and chemotherapy. 6 We did not observe these treatment disparities among patients treated in the DoD health care system.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] As previous studies have demonstrated that black patients with PDAC undergo surgical evaluation, surgical resection, and adjuvant therapy less frequently than white patients, it is possible that differences in pancreatic cancer outcomes observed between races may be the result of differences in access to quality health care. 2,3,5,6,9 Because racial and ethnic minorities are less likely to have health insurance, some have suggested universal health care coverage might help reduce this health care disparity. 10 The Department of Defense (DoD) health care system is unique among health care systems in that all beneficiaries have inexpensive, unlimited access to care.…”
mentioning
confidence: 99%
“…However, many patients still do not receive multimodality therapy, despite evidence for improved survival with its use. [22, 24, 25] Although an increasing number of studies report on both use and effectiveness of neoadjuvant therapy from specialized centers, the use of neoadjvuant therapy in the setting of clearly resectable disease remains a topic of debate. Adjuvant chemotherapy is still given in nearly 90% of patients who received multimodality therapy in the general population.…”
Section: Discussionmentioning
confidence: 99%